Pengaruh Likuiditas, Profitabilitas, dan Leverage Terhadap Financial Distress pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2019-2021 - Priana, Farchan Nugraha; Amin, Moh.; Anwar, Siti Aminah (Universitas Islam Malang, 2024)
The COVID-19 pandemic that has hit the world since December 2019 has become a disaster and economic crisis throughout the world. One of the risks that a company may face is financial distress. There are several financial ratios that can be used to predict financial distress, namely liquidity, profitability and leverage ratios. This research aims to determine the effect of liquidity, profitability, and leverage on financial distress, the effect of liquidity on financial distress, the effect of profitability on financial distress, and the effect of leverage on financial distress. The data used in this research can come from financial reports. The data collection method in this research is document analysis. The population in this research are manufacturing companies on the BEI. The sampling technique used was purposive sampling. The method used in this research is a quantitative method using descriptive statistical analysis, normality analysis, classical hypothesis analysis, multiple segment regression analysis and hypothesis analysis, where data is analyzed using quantitative methods. SPSS. The results of this research show that liquidity, profitability and leverage have a simultaneous effect on financial distress, liquidity has a positive and significant effect on financial distress, profitability has a positive and significant effect on financial distress, and leverage has no effect on financial distress.Keyword: Financial distress, liquidity ratio, profitability ratio, leverage ratio.